Multispecies biofilm in an artificial wound bed--A novel model for in vitro assessment of solid antimicrobial dressings - Kucera, J; Sojka, M; Pavlik, V; Szuszkiewicz, K; Velebny, V; Klein, P (Journal of microbiological methods, 2014)
Wound infections represent a major problem, particularly in patients with chronic wounds. Bacteria in the wound exist mainly in the form of biofilms and are thus resistant to most antibiotics and antimicrobials. A simple and cost-effective in vitro model of chronic wound biofilms applied for testing treatments and solid devices, especially wound dressings, is presented in this work. The method is based on the well-established Lubbock chronic wound biofilm transferred onto an artificial agar wound bed. The biofilm formed by four bacterial species (Staphylococcus aureus, Enterococcus faecalis, Bacillus subtilis and Pseudomonas aeruginosa) was stable for up to 48h post-transplant. The applicability of the model was evaluated by testing two common iodine wound treatments. These observations indicate that this method enables assessing the effects of treatments on established resilient wound biofilms and is clinically highly relevant.
Keywords: jod; exprese genu; Phenotype; bakteriální nálož; Anti-Infective Agents; fenotyp; techniky in vitro; Artificial wound bed; Iodine; In vitro testing; Genes, Bacterial; infekce v ráně; In Vitro Techniques; Wound Infection; Biofilms; Multi-species wound biofilm model; bakteriální geny; obvazy; Bacterial Load; Bandages; Bacteria; Chronic Disease; chronická nemoc; Anti-biofilm substances; Gene Expression; biofilmy; antiinfekční látky